2010
DOI: 10.1597/09-106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nasalance Scores and Nasality Ratings Obtained with Equal Appearing Interval and Direct Magnitude Estimation Scaling Methods

Abstract: No difference was found in the relationship between nasalance and nasality when nasality was rated using EAI as opposed to DME procedures. Nasometer test sensitivity and specificity were similar for EAI- and DME-rated nasality. A linear model accounted for the greatest proportion of explained variance in EAI and DME ratings. Consequently, clinicians should be able to obtain valid and reliable estimates of nasality using EAI or DME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 24 publications
6
44
2
5
Order By: Relevance
“…In the present study, by correlating the nasalance scores with the auditory perceptual judgments, the results showed that, although statistically significant, the correlation was low (between 0.31 and 0.37). These results corroborate with previous findings 16 which also found a low correlation between the two variables, differing, however, with studies that found high 9,11-13 or moderate 14,15 correlations between speech nasality and the nasalance scores.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, by correlating the nasalance scores with the auditory perceptual judgments, the results showed that, although statistically significant, the correlation was low (between 0.31 and 0.37). These results corroborate with previous findings 16 which also found a low correlation between the two variables, differing, however, with studies that found high 9,11-13 or moderate 14,15 correlations between speech nasality and the nasalance scores.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study found high sensitivity and specificity of the method, confirming indications complementing the velopharyngeal evaluation 9 , besides indicating similar sensitivity and specificity even when different perceptual scales are used 15 .…”
supporting
confidence: 61%
See 2 more Smart Citations
“…This result may be explained by the type of scale used to classify hypernasality. As in most studies in the literature, the present study used an ordinal scale, which has been the most widely used both in research and in clinical practice (27,28) . However, due to the psychophysical nature of nasality, high agreement among different raters have been difficult to achieve using this method (29) .…”
Section: Discussionmentioning
confidence: 99%